Case Report: FBN1 mutation screening in South African patients with Marfan syndrome - Mhlongo, F.; Feben, C.; Krause, A.; Carstens, N. (Frontiers in Genetics, 2025)
Marfan syndrome (MFS) is a systemic heritable connective tissue disorder caused by pathogenic variants in the FBN1 gene. Previous studies have documented the clinical utility of FBN1 mutation screening as some nucleotide changes and functional domains are associated with specific clinical presentations, many of which are age dependent. However, molecular testing has not been incorporated into routine clinical service for MFS in South Africa. Here we present clinical phenotypes and molecular confirmation of MFS in a cohort of South African patients. Mutation screening using a targeted next-generation sequencing (NGS) panel identified seven heterozygous likely pathogenic and/or pathogenic FBN1 variants in eleven South African patients with MFS. Two of these variants are novel. This study thus contributes to the description of the mutation spectrum of MFS in Africa and highlights the diagnostic utility and importance of FBN1-based mutation testing, especially in children and for prognostic purposes.